2017
DOI: 10.3390/biom7010015
|View full text |Cite
|
Sign up to set email alerts
|

The Genomic Impact of DNA CpG Methylation on Gene Expression; Relationships in Prostate Cancer

Abstract: The process of DNA CpG methylation has been extensively investigated for over 50 years and revealed associations between changing methylation status of CpG islands and gene expression. As a result, DNA CpG methylation is implicated in the control of gene expression in developmental and homeostasis processes, as well as being a cancer-driver mechanism. The development of genome-wide technologies and sophisticated statistical analytical approaches has ushered in an era of widespread analyses, for example in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
55
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 157 publications
7
55
1
Order By: Relevance
“…Although a strictly linear relationship between GSDME methylation and expression is not anticipated, we would expect that increased methylation leads to decreased gene expression in cancer. The discrepancy in our results and in conflicting findings, make it hard to clearly define the effect of GSDME methylation on its expression, particularly in light of recent studies suggesting that the relation between the 2 could be more complex . One conflicting factor could be miRNAs (mir‐3p and mir26b‐5p) that are known to modulate GSDME expression, and another could be copy number variations (CNVs) that play an important role in complex phenotypes such as cancer .…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…Although a strictly linear relationship between GSDME methylation and expression is not anticipated, we would expect that increased methylation leads to decreased gene expression in cancer. The discrepancy in our results and in conflicting findings, make it hard to clearly define the effect of GSDME methylation on its expression, particularly in light of recent studies suggesting that the relation between the 2 could be more complex . One conflicting factor could be miRNAs (mir‐3p and mir26b‐5p) that are known to modulate GSDME expression, and another could be copy number variations (CNVs) that play an important role in complex phenotypes such as cancer .…”
Section: Discussioncontrasting
confidence: 63%
“…The discrepancy in our results and in conflicting findings, 13,30 make it hard to clearly define the effect of GSDME methylation on its expression, particularly in light of recent studies suggesting that the relation between the 2 could be more complex. 31 One conflicting factor could be miRNAs (mir-3p and mir26b-5p) that are known to modulate GSDME expression, 32 and another could be copy number variations (CNVs) that play an important role in complex phenotypes such as cancer. 33 Moreover, the location of CpG methylation (in or near the island) is crucial to its influence on gene expression such that CpGs located outside the islands have a bigger impact on gene expression than those located within.…”
Section: Discussionmentioning
confidence: 99%
“…Methylation of the cytosine at CpG sites has important roles within the cell in regulating gene expression and silencing (Long et al, 2017). Single-gene and genome sequencing studies have identified that the vast majority of substitution mutations in human cancer occurs at the CpG dinucleotide (Cooper and Youssoufian, 1988;Esteller et al, 2001;Esteller, 2002;Poulos et al, 2017;Pfeifer, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Enhancer methylation has been correlated with gene expression, most frequently in cancer patients but also in healthy individuals [43]. Notably, enhancer methylation is both correlated with increased and decreased gene expression, possibly explaining why we see an enrichment of CpG deamination in both gain and loss of function events [44].…”
Section: Discussionmentioning
confidence: 79%